HPV 16E7 and 48E7 proteins use different mechanisms to target p130 to overcome cell cycle block. Issue 1 (December 2016) - Nor Rashid, Nurshamimi; Yong, Zi; Yusof, Rohana; Watson, Roger
Abstract Background Retinoblastoma like protein 2 (RBL2) or p130 is a member of the pocket protein family, which is infrequently mutated in human tumours. Its expression is posttranscriptionally regulated and largely G0 restricted. We have previously shown that E6/E7 oncoproteins encoded by human papillomavirus (HPV) type 16, which is a high-risk type for cervical cancer development, must target p130 to promote the host cell to exit from quiescence (G0) state and enter S phase of the cell cycle. P130 is associated with the DREAM (DP, RB-like, E2F and MuvB) complex in G0/G1, which prevents S phase progression by repressing transcription of E2F-regulated genes. E7 proteins could potentially disrupt the p130-DREAM complex through two known mechanisms: direct interaction with p130 or induction of cyclin dependent kinase 2 (CDK2) phosphorylation by interacting with its inhibitor, p21CIP1 . Methods In this study we have used p130 mutants deficient in binding the E7 LXCXE domain (p130mE7), unphosphorylatable by CDK2 (p130PM22) or a combination of both (p130PM22/mE7) to investigate these mechanisms used by E7 proteins to disrupt the p130-DREAM complex and promote cell cycle progression. Results We found that HPV16 E7 binding to p130 through its LXCXE domain was absolutely required to disrupt p130-DREAM to promote S phase of the cell cycle, as HPV16 E7 was unable to suppress p130mE7 but could suppress p130PM22. In contrast, the E7 protein encoded by a cutaneous HPV type that lacks a functional LXCXE domain, HPV 48 E7, was also able to disrupt p130-DREAM to promote cell cycling, but through the alternative mechanism. Thus, HPV48 E7 could suppress a cell cycle block imposed by p130mE7, but was unable to suppress p130PM22. Conclusions Overall, these results indicate that suppression of p130 is required for HPV-induced cell cycling, and that different HPV E7 proteins can use alternative mechanisms to achieve this.